Evaluating the correlation between pretreatment 18F-FDG PET/CT metabolic parameters and tumor-infiltrating lymphocyte levels in nonluminal breast cancer and impact on survival - Muge Tamam; Halim Ozcevik; Gamze Kulduk; Merve Nur Acar Tayyar; Gunduzalp Bugrahan Babacan (Pathology and Oncology Research)
Background and ObjectivesThis study aims to evaluate the correlation between Tumor-Infiltrating Lymphocyte (TIL) levels and Fluorine-18 fluorodeoxyglucose (18F-FDG) metabolic parameters, including spleen and bone marrow FDG uptake and tumor heterogeneity in non-luminal breast cancers (NLBC), and to elucidate their association with survival outcomes.MethodsWe retrospectively analyzed data from 100 females with stage 2–4 NLBC who underwent pretreatment 18F-FDG Positron emission tomography-computed tomography (PET/CT). TIL was scored based on Hematoxylin-Eosin-stained specimens and 18F-FDG PET metabolic parameters, including maximum standardized uptake value (SUVmax), mean standardized uptake value (SUVmean), metabolic tumor volume (MTV), total lesion glycolysis (TLG), liver, spleen, and bone marrow FDG uptake were calculated. Heterogeneity Index (HI)1, HI2, and HI3 indices were analyzed with FDG metabolic parameters. The association between these factors and overall survival was analyzed using multivariate Cox regression models.ResultsTIL showed weak negative correlations with tumor size, tumor (T), and metastasis (M) stages. No significant correlation was found between TIL levels and overall SUV values. However, in stage 4, TIL correlated positively with liver, spleen, and bone marrow SUV values and negatively with heterogeneity indices (HI2, HI3). Higher tumor size, HI values, and Bone marrow-to-liver ratio (BLR) SUVmean were associated with increased mortality. A TIL cut-off value of <5 was linked to significantly worse survival.ConclusionOur study demonstrates a strong connection between TIL, FDG metabolic parameters, and tumor heterogeneity, particularly in advanced NLBC. Although TIL is not generally associated with SUV values, its association with certain metabolic and heterogeneity indices suggests that it is important in influencing survival. Further research involving larger cohorts and diverse breast cancer subtypes is needed to validate these results.